2023
DOI: 10.1142/s0217979223502521
|View full text |Cite
|
Sign up to set email alerts
|

Entropy optimized flow of hybrid nanofluid with partial slip boundary effects and induced magnetic field

Abstract: There are various implementations of common fluids in industrial and chemical processes. With the cooperation of the nanoparticles, the lower thermal properties of such fluids can be augmented. By using a new kind of nanofluid namely hybrid nanofluid, the heat transfer rate of such fluids can be boosted more quickly. The main intention of this research is on entropy analysis in the stagnant point flow of a hybrid nanofluid. The mixed convection nonlinear thermal radiative flow on a stretchable vertical sheet i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…According to 2 nd law of thermodynamics, rate of entropy generation per unit volume can be formulated as given in [27,33]. Where, the impacts of induced magnetic field, viscous dissipation and heat generation are under assumption.…”
Section: Analysis Of Entropy Generationmentioning
confidence: 99%
See 3 more Smart Citations
“…According to 2 nd law of thermodynamics, rate of entropy generation per unit volume can be formulated as given in [27,33]. Where, the impacts of induced magnetic field, viscous dissipation and heat generation are under assumption.…”
Section: Analysis Of Entropy Generationmentioning
confidence: 99%
“…Subjected no‐slip wall conditions are [27, 33]: 0trueubadbreak=Uwgoodbreak=cx,Tgoodbreak=Tw,vgoodbreak=0,H1ygoodbreak=0,H2goodbreak=00.33emat0.33emygoodbreak=0,0trueuU,TT,H1goodbreak=He()xH0x0.33emas0.33emy.$$\begin{equation} \def\eqcellsep{&}\begin{array}{l} \displaystyle u = {U}_w = cx,T = {T}_w,v = 0,\frac{{\partial {H}_1}}{{\partial y}} = 0,{H}_2 = 0\ at\ y = 0, \\[12pt] \displaystyle u \to U_\infty ,T \to {T}_\infty,{H}_1 = {H}_e\left(x\right) \to {H}_0x\ as\ y \to \infty. \end{array} \end{equation}$$…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…With the significance of the variable magnetic field, the properties of the micropolar fluid on distinct mediums were explored by Nadeem et al 14 Through a stretched, slender medium, the thermal analysis and flow mechanism based on magnetic properties in a fluid containing distinct nanoparticles were addressed by Elsebaee et al 15 Recent studies on the magnetized flow of hybrid nanofluids can be found in ref. 16–24.…”
Section: Introductionmentioning
confidence: 99%